2017
DOI: 10.1167/iovs.16-20105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Ellipsoid Zone Intensity in Phenotypic Variations of Intermediate Age-Related Macular Degeneration

Abstract: Citation: Gin TJ, Wu Z, Chew SKH, Guymer RH, Luu CD. Quantitative analysis of the ellipsoid zone intensity in phenotypic variations of intermediate age-related macular degeneration. Invest Ophthalmol Vis Sci. 2017;58:207958: -208658: . DOI:10.1167 PURPOSE. Reduction of the ellipsoid zone (EZ) intensity has been reported in eyes with agerelated macular degeneration (AMD). This study determined whether overall EZ intensity, in retinal locations undisturbed by pathologic features, is associated with the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 55 publications
(84 reference statements)
3
39
0
Order By: Relevance
“…In agreement with changes reported in the ellipsoid zone in AMD [22], it would make sense to expect changes in the outer layers [44] such as the MZ and OS. With a decrease in MZ thickness in the RPD group compared to in the drusen ≥125-µm group, the greatest differences were found in the total mean values and in the nasal region.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with changes reported in the ellipsoid zone in AMD [22], it would make sense to expect changes in the outer layers [44] such as the MZ and OS. With a decrease in MZ thickness in the RPD group compared to in the drusen ≥125-µm group, the greatest differences were found in the total mean values and in the nasal region.…”
Section: Discussionsupporting
confidence: 80%
“…With improved imaging techniques, the deposits located in the subretinal or pre-RPE space [19], termed "reticular pseudodrusen" (RPD) or "subretinal drusenoid deposits," are more frequently identified [18,19,22]. With an apparent predominance in the superotemporal region of the macula, and clearly identifiable on spectraldomain optical coherence tomography (SD-OCT) [23] in a position anterior to the RPE cell monolayer [18], RPD appear to be relevant in the prognosis and evolution of AMD [24][25][26][27][28].…”
mentioning
confidence: 99%
“…Although the prognosis of welding-induced photic retinal injury is usually good, permanent complications are sometimes reported,9 and this difference in sequelae may reflect the severity of exposure and injury. Absence or disruption of the ellipsoid zone is known to be closely correlated with prognosis of visual acuity and disease severity 13 14. In solar retinopathy cases, decreased central foveal thickness and full-thickness disruption beneath the fovea observed on OCT could be associated with permanent visual acuity loss 15.…”
Section: Discussionmentioning
confidence: 99%
“…For the conventional manual quantification approach, both the EZ and the ELM peak was visually identified from the reflectivity profile in each predetermined ROI and their peak intensity values were obtained manually. 16 , 17 , 20 The manual method was performed by a single examiner (S.T.). For the automated method, the EZ and the ELM peak intensity was determined using an algorithm developed in MatLab software.…”
Section: Methodsmentioning
confidence: 99%
“…The same group also showed that the rEZR was significantly reduced in eyes with intermediate (i) AMD, particularly in eyes with reticular pseudodrusen and pigmentary changes, compared with the normal control eyes. 15 , 16 These findings suggest that rEZR might have a role in AMD characterization and monitoring disease progression. However, the rEZR data in those studies were obtained manually from a limited number of locations on a single OCT line scans (B-scan) through the fovea.…”
Section: Introductionmentioning
confidence: 93%